Selection and identification of a novel bone-targeting peptide for biomedical imaging of bone - Jinho Bang (Nature Portfolio, 2020)
Abstract The global burden of bone-related diseases is increasing in the aging society; thus, improved bone targeted imaging for their early identification and treatment are needed. In this study, we screened novel peptide ligands for hydroxyapatite, a major inorganic component of teeth and bones, and identified a peptide enabling in vivo bone targeting and real-time fluorescence bone detection. To isolate peptides highly specific for hydroxyapatite, we used negative and positive selection from a randomized 8-mer peptide phage library and identified hydroxyapatite-specific peptides (HA-pep2, HA-pep3, and HA-pep7). Among these three peptides, HA-pep3 showed the highest binding capacity and superior dissociation constant towards hydroxyapatite surfaces over time (~ 88.3% retained on hydroxyapatite after two weeks). Furthermore, HA-pep3 was highly specific for hydroxyapatite compared to other calcium salt-based materials. Using this superior specificity, HA-pep3 showed higher accumulation in skull, spine, and joints in comparison with scrambled control peptide during real-time whole-body imaging. Ex vivo analysis of the major organs and bone from mice demonstrated that the fluorescence intensity in bone was about 3.32 folds higher in the case of HA-pep3 than the one exhibited by the scrambled control peptide. Our study identified a novel approach for targeting ligands for bone specific imaging and can be useful for drug delivery applications.